Implantación de un sistema de Red inalámbrica en el Centro Asociado del Catón La Maná de la Universidad Técnica de Cotopaxi para la interconexión de las dependencias y centros de computo - Alvarez León, Victor Patricio (2008)
In the last year, the wireless Local Area Network (WLAN), are getting a lot of popularity that is increasing according to their service development and also because of the new applications that are discovered for them. The (WLAN) permit their users to accede to some information and resources in a real time without the necessity of being physically connected to a specific place. With the WLANs, the network, by itself, it is mobile and eliminates the necessity to use cables and it establishes new applications adding flexibility to the network, and the most important, it increases the productivity and efficiency in the entities where it is installed. A user inside of a WLAN network can receive and transmit voice, data and videos inside of buildings, university grounds and also on Metropolitan Areas. This thesis presents the implementation of a wireless network for the Associated Centre from Cotopaxi Technical University in La Maná Canton. Its goal is to have confident access to network and to the services that this Associated Centre presents. For its development is used an operative system based on Linux which is robust, stable and multiuser, multitask, multiplatform and with a great capacity to manage networks like: the CentOS 4.5. Likewise, an implementation of services was made such as DHCP (Protocolo de Configuración Dinámica de Máquinas), SQUID (Servidor Intermedio Proxy), RADIUS (Remote Authentication Dial In User Service) that is a protocol of authentication and authorization for application of access to the mobility or IP network, its objective is to establish the security parameters to obtain a safe connection. The wireless network that actually is installed in the Associated Center from Cotopaxi Technical University in La Maná Canton was proved in an application of access to the internet, connection with the wired network and interchange of information among networks, since the middle points until the most extreme ones of the university field where the obtained results from the proofs, show a good balance between the quality of the service and the security.